NEUROPROTECTIVE EVALUATION OF TANGERETIN: INSIGHTS FROM INSILICO AND IN VITRO STUDIES ON RAT GLIOMA CELL LINE - MONICA P; SRI VARSHINI BAYYANA VN; NATTYA PARAMESH; THILAK G B (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: The objective of the study is to investigate the neuroprotective effect of tangeretin by in silico molecular docking with GluN2B-containing N-methyl-D-aspartic acid (NMDA) receptor and in vitro assays using the C6 cell line. Methods: Phytochemicals sourced from PubChem and the ZINC database were docked to the GluN2B subunit-containing NMDA receptor (NMDAR) (Protein Data Bank: 5EWJ) using PyRx. Absorption, distribution, metabolism, excretion, toxicity properties, and blood–brain barrier (BBB) permeability were assessed through SwissADME and Online BBB prediction server. With the molecule of interest, in vitro studies such as MTT, apoptosis assay, gene expression of Bcl-2, Bax-2, caspase-3, and poly(ADP-ribose) polymerase 1 were detected. Results: The study explored tangeretin as a therapeutic agent targeting the GluN2B subunit of NMDARs. Docking studies showed strong binding affinity (−7.3 kcal/mol) and interactions mimicking ifenprodil. Tangeretin complied with Lipinski’s rule, high GI absorption (98.478%), BBB penetration, and non-mutagenicity, supporting its use for neurodegenerative diseases. In vitro assays confirmed >85% viability at 1000 μg/mL (85.65 ± 1.07% at 1000 μg/mL) and anti-apoptotic effects by significantly upregulating Bcl-2 and downregulating Bax and Caspase-3. Conclusion: Tangeretin demonstrated significant neuroprotective potential by inhibiting NMDAR-mediated apoptosis, increasing anti-apoptotic gene expression. With its high gastrointestinal absorption, BBB permeability, and low cytotoxicity, tangeretin emerges as a safe therapeutic candidate for treating neurodegenerative diseases. This study elucidates molecular and cellular effects, laying the foundation for developing tangeretin-based neuroprotective therapies.